Natural History and Implantable Cardioverter‐Defibrillator Implantation After Revascularization for Stable Coronary Artery Disease With Depressed Ejection Fraction. Issue 12 (7th October 2015) - Lewis, Geoffrey F.; Harless, Adam C.; Vazquez, Lauren; Abi‐Samra, Freddy M.; Bernard, Michael L.; Khatib, Sammy; Polin, Glenn M.; Morin, Daniel P.
ABSTRACT: Background: Following revascularization, most payors require 3 months of medical therapy, followed by left ventricular ejection fraction (LVEF) reassessment, before implantable cardioverter‐defibrillator (ICD) implantation possibly contributing to incomplete follow‐up and suboptimal utilization of ICD therapy. The natural history of these patients, and their fate regarding ICD implantation, is unknown. Hypothesis: We hypothesized that a waiting period after revascularization for stable CAD results in missed opportunities to provide care with regard to ICD implantation. Methods: We followed patients with LVEF ≤ 35% and no ICD who underwent revascularization (coronary artery bypass grafting [CABG] or percutaneous coronary intervention [PCI]) for stable CAD. Follow‐up used chart review and scripted telephone interviews. Results: Among 3164 revascularized patients (2198 [69%] PCI, 966 [31%] CABG), only 62 (2%; 33 [53%] male, age 67 ± 12 y, LVEF 28% ± 6%) had stable CAD, depressed LVEF, and no ICD. Over 35 ± 19 months, 35 (56%) of these 62 patients were no longer candidates for ICD based on improved LVEF, 14 (23%) received an ICD, 5 (8%) declined ICD despite physician recommendation, 3 (5%) were not offered ICD despite continued eligibility, 2 (3%) died, 1 (2%) was not a candidate due to substance abuse, and 1 (2%) had ICD implantation temporarily deferred. Only 1 (2%) was lost to follow‐up. Conclusions: Following revascularization for stable CAD with depressed LVEF, ≥50% of patients' ventricular function improved enough to make ICD implantation unnecessary. A waiting period after revascularization prior to ICD implantation appears appropriate and does not significantly negatively impact follow‐up or the rate of appropriate ICD implantation.